The Effect of Cooperative Learning Type Team Assisted Individualization Assisted by Teaching Aids on Students' Mathematical Representation Ability - Isni Maulia Pancasilawati; Habibullah Habibullah; Salviana Salviana (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
This research aimed to know the effect of cooperative learning type team assisted individualization assisted by teaching aids on students' mathematical representation ability. The research method used was a quasi-experiment with a one-group pretest-posttest design. The subjects of this research were 33 students from one of the State Junior High School in Cirebon using a sampling technique, namely purposive sampling but not using a control class. The data collection technique were carried out by pretest, posttest, and student activity observation sheets. The research data were analyzed using the average gain score analysis and correlation test. The results showed that there were an effect of cooperative learning type team assisted individualization assisted by teaching aids on students' mathematical representation ability. This can be seen from the increase in the mathematical representation ability of students at each evaluation that has been carried out with an increase in the average value of 51.61, and the student activity process that has increased at each meeting with an average percentage gain of 76.03% with a good categoryÂ Â